Computational systems biology - Eils, Roland; Kriete, Andres (Elsevier/AP, 2014)
This comprehensively revised second edition of Computational Systems Biology discusses the experimental and theoretical foundations of the function of biological systems at the molecular, cellular or organismal level over temporal and spatial scales, as systems biology advances to provide clinical solutions to complex medical problems. In particular the work focuses on the engineering of biological systems and network modeling.Logical information flow aids understanding of basic building blocks of life through disease phenotypes.